Venturi Optimization and Local Pressure Method for Measuring Supercritical CO2 Flow in Downhole - Chunfeng Zheng; Wanyou Yang; Dedong Xue; Lei Kou; Sheng Wang; Zhengyang Chen; Shijiao Jia; Chao Yuan (Energies)
This study is dedicated to exploring and verifying the application of a miniature Venturi sensor for measuring the flowrate of supercritical CO2 and associated gas in downhole environments. With the rapid development of CO2 gas injection technology and Carbon Capture, Utilization, and Storage (CCUS) technology, the demand for accurate measurements of a CO2 and CH4 mixed-medium flowrate is increasing. This paper combines theoretical analysis, simulation design, and experimental validation to determine the optimized structure of a miniature Venturi and to select appropriate pressure sensors, comparing the accuracy of the Local Pressure Method (LPM) and Differential Pressure Method (DPM) in measuring differential pressure. The experiments were conducted using the water flow calibration facility and the gas–liquid two-phase flow rig at Tianjin University, comparing the LPM based on Keller pressure sensors with the DPM based on EJA110A transmitters. The results indicate that the relative error range of the differential pressure measurement is −16.64% to −0.72%, and the absolute error range is −5.19 kPa to −0.24 kPa, meeting the measurement requirements for underground applications. This validates the rational design of the miniature Venturi sensor and the feasibility of using the LPM in downhole.